Literacki obraz świata: polisemiczność reprezentacji - Tokarz, Bożena (Slavistična revija, 2006)
Non-literary reality is never directly present in literature except in verbal texts taken from it. It materializes as an illusion, image, testimony, and presentation. The most creative for of mental representation is a presentation that allows a literary Work to oscilate between illusion and testimony, "pretense ad reference". Among the rhetoric forms of literary representations, methaphor and ficton most profoundly mirror the cultural changes that took place in the 20th cnetury.
Keywords: artistic representation; cognitivism; kognitivizem; literatura; literature; umetniška reprezentacija